BATOBO SEBAGAI SEBUAH SISTEM SOSIAL DALAM BERTANI PADI SAWAH DI DESA PULAU MUNGKUR KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Adiguna, Aan; ', Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT This research was carried out in Pulau Mungkur Village, Gunung Toar District, Kuantan Singingi Regency. The aim of this research is to explain the aims and procedures for Batobo in Pulau Mungkur Village, Gunung Toar District, Kuantan Singingi Regency and to determine the organizational structure and systems in Batobo activities in Pulau Mungkur Village, Gunung Toar District, Kuantan Singingi Regency. The research subjects and informants involved in this research were 7 people, including 1 key informant, namely from Ninik Mamak in Pulau Mungkur Village and 6 subjects from the Batobo group in Pulau Mungkur Village, Gunung Toar District, Kuantan Singingi Regency. This research use desciptive qualitative approach. The methods used are observation, documentation and in-depth interviews. Checking data from various sources is carried out through technical triangulation as an effort to increase the researcher's understanding of what has been found. The results of the research carried out show that the aim of Batobo is to speed up the work of rice fields compared to individuals. In Batobo in Pulau Mungkur Village there are procedures for activities, the first is Malawe, namely hoeing the rice fields for the first time, then Mangamolan, namely hoeing for the second time, next,malunyah, namely trampling the fields, the aim of which is to loosen and facilitate the rice planting process, and finally rice harvest process. In Batobo there is a Ninik Mamak who determines the time to go down to the fields, there is a Batobo Chairman who organizes the group, there is a Tobo Secretary and also a Treasurer in the Batobo group. Keywords: Batobo, Social System, Rice Fields